Study of Learning Process Using the Provus Evaluation Model at Keputran 2 Elementary School Yogyakarta - Suyono Suyono; Alnurrizki Muthfisari; Steffi Permata Dewi (TAMANSISWA INTERNATIONAL JOURNAL IN EDUCATION AND SCIENCE, 2025)
This study aims to analyze the learning process at Keputran 2 Elementary School Yogyakarta using the Provus evaluation model. The primary objective is to identify discrepancies between established process standards and their implementation in classroom practices. This research employed a qualitative approach with a case study design. Data were collected through classroom observations, in-depth interviews with teachers and the principal, and document analysis, including teaching modules and curriculum documents. The Provus evaluation model was applied through four stages: design, installation, process, and product. The findings reveal that although the school has generally implemented the learning process standards in accordance with ideal procedures, several discrepancies remain in lesson planning, instructional implementation, and assessment practices. Learning activities tend to be less varied, the integration of instructional media and technology remains limited, and assessment planning has not fully adhered to standard procedures. Therefore, continuous professional development for teachers and improved implementation of student-centered learning are necessary. This study concludes that the Provus evaluation model is effective in identifying discrepancies and providing actionable recommendations to enhance the quality of elementary education.